Knowledge, perceived risk, and preventive behaviors amidst Covid-19 Pandemic among dental students in Malaysia - Ismail, Azlini; Ismail, Nur Hanisah; Abu Kassim, Nur Yasrin Maisarah; Lestari, Widya; Ismail, Ahmad Faisal; Sukotjo, Cortino (MDPI, 2021)
Purpose: Coronavirus disease 19 (COVID-19) has affected dental education in Malaysia. However, studies on dental students’ knowledge, perception, and behaviors with regards to COVID-19 are very limited. Thus, this study aims to determine the knowledge status, perceived risk, and preventive behaviors of dental students in Malaysia regarding COVID-19. Methods: A cross-sectional study was conducted among students from 13 dental schools across Malaysia using online questionnaires. Results: From 355 respondents, 93.5% obtained a high score of knowledge of COVID-19. Female respondents scored higher than males in perceived risks and preventive behaviors. Chinese respondents scored highest in knowledge, while Malay respondents had the highest perceived risk score. The mean preventive behavior score did not vary across ethnicity. On-campus students scored higher in knowledge and perceived risk whereas off-campus students practiced more preventive behaviors. Clinical students’ knowledge score was higher than preclinical students. Final year students scored higher in knowledge and perceived risk compared to their juniors. Conclusion: The majority of dental students have good knowledge and a high perceived risk of COVID-19, and they practiced most of the preventive behaviors. However, the latest information on this disease should be incorporated into dental schools’ curriculums and updated periodically.